HISTORY OF RAILWAYS IN KYRGYZSTAN (Scientific journal of the Fergana State University, 2023)
In the world, communication and transport structures of certain countries and regions have long become objects of study. In particular, it is important to study as priority problems the state in the independent period of socio-economic life, the sectors of the national economy of the Republic of Kyrgyzstan, which is rich in terms of material and human resources of the territory of Central Asia, including the role of the transport system, railways in economic life. of the republic, the stages of their development, the position of the industry in industry, its impact on the standard of living of the population, the processes of improving the branches and networks of railways. The purpose of the study is to highlight the history of railway transport in Kyrgyzstan in independent years and the changes that have taken place in the industry. The article uses the principles of historicism, consistency, objectivity, civilizational approach to the problem, as well as methods of comparative and problem-chronological analysis. The practical results of the study are as follows: for the first time since domestic historiography, the impact of political and economic changes on the railway industry in the current period has been studied, proposals and recommendations on certain issues have been developed; shows the theoretical conceptual foundations for studying the history of this industry in the region based on the identification and comparative analysis of archival materials, statistical data and materials of periodicals related to the history of railways in Kyrgyzstan.